Association between prenatal exposure to alkylphenols and intelligence quotient among preschool children: sex-specific effects - Jinghua Long; Jun Liang; Tao Liu; Huishen Huang; Jiehua Chen; Qian Liao; Lixiang Pang; Kaiqi Yang; Manlin Chen; Qian Chen; Xiaorong Huang; Qihua Zhu; et al. (Environmental Health, 2024)
Abstract Background While prenatal exposure to alkylphenols (APs) has been demonstrated to be associated with neurodevelopmental impairments in animals, the evidence from epidemiological studies remains limited and inconclusive. This study aimed to explore the link between AP exposure during pregnancy and the intelligence quotient (IQ) of preschool children. Methods A total of 221 mother-child pairs from the Guangxi Zhuang Birth Cohort were recruited. Nonylphenol (NP), 4-tert-octylphenol (4-T-OP), 4-n-nonylphenol (4-N-NP), and 4-n-octylphenol were measured in maternal serum in early pregnancy. Childhood IQ was evaluated by the Fourth Edition of Wechsler Preschool and Primary Scale of the Intelligence at 3 to 6 years of age. The impact of APs on childhood IQ were evaluated by generalized linear models (GLMs), restricted cubic spline (RCS), and Bayesian kernel machine regression (BKMR). Results In GLMs, prenatal exposure to NP and the second tertile of 4-T-OP exhibited an inverse association with full-scale IQ (FSIQ) (β = -2.38; 95% CI: -4.59, -0.16) and working memory index (WMI) (β = -5.24; 95% CI: -9.58, -0.89), respectively. Prenatal exposure to the third tertile of 4-N-NP showed a positive association with the fluid reasoning index (β = 4.95; 95% CI: 1.14, 8.77) in total children, as well as in girls when stratified by sex. A U-shaped relationship between maternal 4-T-OP and WMI was noted in total children and girls by RCS (all P nonlinear < 0.05). The combined effect primarily driven by NP, of maternal AP mixtures at concentrations above the 50th percentile exhibited an inverse trend on FSIQ in total children and girls in BKMR. Conclusions Prenatal exposure to various APs affects IQ in preschool children, and there may be nonmonotonic and sex-specific effects. Further investigation across the population is required to elucidate the potential neurotoxic effects of APs.